Clinical Decision-Making and Use of Clinical Decision Support When Clinicians are Fatigued in an Emergency Department: A Qualitative Study - Ozkaynak, Mustafa; Cook, Paul F.; Sarabia, Cristian; Daley, Trystn; Yu, Amy; Mistry, Rakesh D.; Schmidt, Sarah K. (Applied Clinical Informatics, 2025)
Clinicians' occupational fatigue can lead to suboptimal decisions that do not align with evidence-based guidelines or patient needs.Examining the effects of occupational fatigue on (1) clinical decision making and (2) the use of clinical decision support (CDS) in a pediatric emergency department (ED).We interviewed 30 pediatric ED clinicians from a single site. Clinicians included physicians and advanced practice practitioners. The interviews were semi-structured and guided by the dual-processing model. Data were qualitatively analyzed.Four main themes emerged from our analysis: (1) fatigue is a dynamic state and has multiple reasons; (2) fatigue affects decision-making in ED care; (3) fatigue affects the use of CDS; (4) fatigue affects a clinician's productivity and outcomes. We developed a conceptual framework that highlights the effects of fatigue on outcomes in the ED setting.In EDs, fatigue is inevitable because of high clinical acuity and the rapid pace of decision-making. Our study highlighted an important need in EDs to support narrative decision-making. Narrative decision-making requires clinicians to make analytical decisions, as opposed to relying on intuition in providing care. Organizational redesign and informatics-based interventions initiatives could be useful to mitigate the effects of fatigue. Rigorous evaluation approaches that account for clinicians' fatigue would improve the usability and usefulness of organizational interventions (e.g., CDS) that improve quality and safety.
Keywords: dual processing; requirements analysis and design; implementation and deployment; burnout; sociotechnical aspects of information technology